Investigation on complementarity between total mesorectal excision and radical resection in relation to postoperative local recurrence in patients receiving anus-reserve operation on rectal cancer - Liu, Kai; Zhao, Peng; Zhuang, Yan; Yue, Xin; Liu, Jianzhong; Dong, Xinshu; Hao, Xishan (The Chinese-German journal of clinical oncology, 2007)
Objective： To investigate the difference and complementarity between total mesorectal excision （TME） and radical resection in relation to postoperative local recurrence in patients receiving anus-reserve operation on rectal cancer. Methods： Clinical data of 81 cases during a period from 1975 to 2001 were retrospectively analyzed. Results： In the 81 cases with local recurrence, 49 of them laid to anastomosis and mesorectum, 17 lymph nodes and 15 multi-site relapse. The choice of operative procedure included abdominoperineal resection in 58 cases, Hartmann＇s operation in 4 cases, simple double-pelvic stoma in 12 cases, exploration in 7 cases, and total pelvic or rear-pelvic resection in combination with other organs in 6 cases. The rate of resection was 84.0% （68/81）. 32 cases reached clinical radical degree, and the rate of radical resection was 39.5% （32/81）. The 5-year survival rate was 34.4% （11/32）. Conclusion： Based on actual condition of the patients, attention to radical resection and total mesorectal excision are necessary, and reasonable adoption of the operative procedure could reduce the local recurrence of rectal cancer.